2018
DOI: 10.1119/1.5006775
|View full text |Cite
|
Sign up to set email alerts
|

One step beyond the electric dipole approximation: An experiment to observe the 5p → 6p forbidden transition in atomic rubidium

Abstract: An advanced undergraduate experiment to study the 5P3/2→6P3/2 electric quadrupole transition in rubidium atoms is presented. The experiment uses two external cavity diode lasers, one operating at the D2 rubidium resonance line and the other built with commercial parts to emit at 911 nm. The lasers produce the 5s→5p→6p excitation sequence in which the second step is the forbidden transition. Production of atoms in the 6P3/2 state is observed by detection of the 420 nm fluorescence that results from electric dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For the two spectra one clearly observes the two expected lines that result from an excitation sequence 5s give place to the dipole-forbidden transitions appearing at a different frequency to those obtained with the maximum F 2 preparation [23]. The strongest of these velocity-selected non-dipole transitions results from the F → F → F excitation chain (2 → 2 → 2 in 87 Rb and 3 → 3 → 3 in 85 Rb).…”
Section: Results Comparison Between Experiments and Theorymentioning
confidence: 76%
“…For the two spectra one clearly observes the two expected lines that result from an excitation sequence 5s give place to the dipole-forbidden transitions appearing at a different frequency to those obtained with the maximum F 2 preparation [23]. The strongest of these velocity-selected non-dipole transitions results from the F → F → F excitation chain (2 → 2 → 2 in 87 Rb and 3 → 3 → 3 in 85 Rb).…”
Section: Results Comparison Between Experiments and Theorymentioning
confidence: 76%
“…The experimental apparatus has been previously described in detail [31,32]. Figure 7 is presented here to point out its basic features.…”
Section: Methodsmentioning
confidence: 99%
“…Levels |1 and |2 correspond to the ground state 5S with an appropriate choice of the excitation light polarization. Furthermore, in [32,36] it is demonstrated that the choice of the relative polarization states of the two excitation beams can be utilized to tailor the excitation paths at the level of the magnetic structure of the atoms. Particularly, in the experiments presented on this work a parallel-linear polarization configuration for the preparation and probe beams was employed.…”
Section: The Physical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its simplicity, velocity-selective spectroscopy with diode lasers is the ideal framework to achieve this. Our research group has reported a technique capable of resolving hyperfine levels together with their magnetic spin projection in atomic rubidium at room temperature [22,23], while Chan et al developed a similar velocity-selective spectroscopic method to resolve E2 transitions in cesium [24]. This work extends the reach of application of E2 transitions providing an ideal probe for performing an in-depth investigation of the dynamics of an atomic system interacting with radiation fields.…”
Section: Introductionmentioning
confidence: 99%